A Living Text between the Editions and its Manuscripts: (A Living Text between the Editions and the Manuscripts) - Cucu Surahman (Universitas Negeri Jakarta, 2020)
This article studies the process of transmission of Qaṣīdah Burdah texts of al-Buṣīrī. This study is carried out by comparing some manuscripts of it with the editions available now. This effort aims to know the process of transmission of knowledge from one generation to another and know how knowledge as the core of civilization is maintained from time to time. This study will scrutinize both the uniformity and the difference of the text; from its handwriting form to a living printed text nowadays. This article is intended to look at both the internal history of texts and the history of reception. Having evaluated the editions and collated the manuscripts of al-Buṣīrī’s Qaṣīdah Burdah preserved in the library of Leiden University, I conclude that there are no significant differences between the editions available nowadays and the manuscripts. The differences only relate to technical matters, such as the division of chapter and the way of reciting.